PENGARUH ROTASI JABATAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN: Survey pada Karyawan Bagian Produksi di Koperasi Peternakan Sapi Bandung Utara Jawa Barat - Beppy Noor Ferdianzah, - (2011)
This study aims to determine the influence of rotation of the position of Employee Productivity in Section Production in Cattle Farming Cooperative of North Bandung West Java. The research method used in this research is descriptive method and verikatif the method of research to create a picture of the situation or event. Sampling technique used in this study sample is saturated with accidental random sampling technique.The sample in this study were 70 employees Cattle Farming Cooperative of North Bandung West Java. Analysis of the data in this study using simple linear regression analysis techniques.This study analyzes the influence of rotation Position on Employee Productivity in Section Production in Cattle Farming Cooperative of North Bandung WestJava. The results showed that the variables X Roatasi Position as a positive influence on Y, ie Employee Productivity in Section Cooperative Ranch Cattle Production in North Bandung West Java. Rotation influences the position of overall employee productivity amounted to 64.5% while the other variables that affect employee productivity 35.5%